kualitas kualias layanan dan harga pengaruhnya terhadap kepuasan pelanggan: kualias layanan dan harga pengaruhnya terhadap kepuasan pelanggan - Evan andrianto Evan adrianto; Agus Raikhani; Linda Ratnasari (eBA Journal: Journal Economic, Bussines dan Accounting, 2022)
Abstract Customer satisfaction is an after-purchase evaluation, if customer satisfaction is achieved, customer loyalty will arise. The purposed of this studied is to examined the effect of service quality and price on customer satisfaction. This study used multiple regression analysis on respondents namely customers using non-probability sampling technique as a sampling method using a questionnaire for data collection. The result of this research revealed that service quality and price with simultan test have effect to customer satisfaction of Kirana Tour and Travel Malang. As parcial system analysis service quality has effect to customer satisfaction. It is also happen to price who have influence to customer satisfaction of Kirana Tour and Travel Malang. The service quality is the most influence variable towards the customer’s satisfaction . Keywords: Service Quality, Price and Customer Satisfaction.